Mineral Indicators - Aluminum (The National Institute for Occupational Safety and Health (NIOSH), 1979)
In October, the Aluminum Company of America restarted the fourth of seven pot-lines at its Point Comfort, Tex. primary aluminum smelter. The price of primary aluminum ingot, as quoted by American Metal Market, was increased from a range of 60.5 to 63.0 cents per pound at the end of September to a range of 66.0 to 66.5 cents per pound at the end of October. BERYLLIUM On October 15, Brush Wellman, Inc., of Cleveland, one of two U.S. producers of primary beryllium products, announced a planned $6 million expansion of its extraction plant at Delta, Utah, increasing the plant?s capacity to extract beryllium from bertrandite ore by 25%. Another $5 million will be spent on two mine expansion programs in Jaub and Millard Counties, Utah. Other mineral claims and 1 eases he 1 d by The Anaconda Company will be taken over by Brush Wellman through lease or purchase. This expansion, when completed in 1981, will decrease U.S. dependence on imported beryl ore.